Randomized phase III study of 2 cisplatin‐based chemoradiation regimens in locally advanced head and neck squamous cell carcinoma: Impact of changing disease epidemiology on contemporary trial design. Issue 11 (29th October 2014) - Rodriguez, Cristina P.; Adelstein, David J.; Rybicki, Lisa A.; Savvides, Panayiotis; Saxton, Jerrold P.; Koyfman, Shlomo A.; Greskovich, John F.; Yao, Min; Scharpf, Joseph; Lavertu, Pierre; Wood, Benjamin G.; Burkey, Brian B.; et al.
Abstract Background Chemoradiotherapy results in excellent outcomes in locally advanced head and neck squamous cell carcinoma (HNSCC). This trial compared 2 chemoradiotherapy regimens. Methods Patients with locally advanced HNSCC were treated with radiation (70–74.4 Gy), and randomized to arm A: cisplatin 100 mg/m2 on radiotherapy (RT) days 1, 22, and 43, or arm B: cisplatin (20 mg/m2/day) and 5‐fluorouracil (5‐FU; 1000 mg/m2/day) continuous 96‐hour infusions on RT weeks 1 and 4. The primary endpoint was relapse‐free survival (RFS). Results Between February 2008 and October 2011, 69 patients were enrolled in this study. The study prematurely closed when a scheduled interim analysis showed superior outcomes in both arms and futility of continuation. Eighty‐three percent of patients had oropharyngeal cancer, of these, 86% were human papillomavirus (HPV)/p16+. The 3‐year Kaplan–Meier outcome estimates (median follow‐up, 41 months) for arms A and B were: RFS 87% versus 80% (p = .24), overall survival 97% versus 85% (p = .013), locoregional control 96% versus 94% (p = .52), and distant metastatic control 91% versus 87% (p = .9). Conclusion Multiagent was not superior to single‐agent chemoradiotherapy. Overrepresentation of HPV/p16+ patients resulted in better than expected outcomes. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1583–1589, 2015